Heart and lung morphometry in Wistar rats infected with canine leptospira during pregnancy - Maria De Jesus Monzón Tamargo; Manuel Guillermo Peterssen Sánchez; Javier Joaquín Pérez Cardoso; Xiomara González García; Susana González Freije (Revista de Ciencias Médicas de Pinar del Río, 2019)
Introduction: leptospirosis is a zoonosis of wide-ranging distribution worldwide that causes great losses to human health.